Some results on fixed and coincidence points for pairs of maps in metric spaces (1993)
Following ideas of Dugundji and Granas, some general results are established on the existence of fixed and coincidence points for a pair of maps on metric spaces. Conditions on the continuity or the commutativity of the maps are expressly avoided.